2023
DOI: 10.3390/nano13040669
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Reinforcement of ABS with Optimized Nano Titanium Nitride Content for Material Extrusion 3D Printing

Abstract: Acrylonitrile Butadiene Styrene (ABS) nanocomposites were developed using Material Extrusion (MEX) Additive Manufacturing (AM) and Fused Filament Fabrication (FFF) methods. A range of mechanical tests was conducted on the produced 3D-printed structures to investigate the effect of Titanium Nitride (TiN) nanoparticles on the mechanical response of thermoplastic polymers. Detailed morphological characterization of the produced filaments and 3D-printed specimens was carried out using Atomic Force Microscopy (AFM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…[125] Some studies have also found that nanoparticles of different particle diameters [132] and shapes can affect the mechanical properties of materials. Besides, researchers often use metal nanoparticles to enhance the mechanical properties of polymer materials, [133] such as Fe 2 O 3 nanoparticles, [134] gold nanoparticles, [135,136] ZrO nanoparticles, [137] titanium dioxide nanoparticles [138] and CuS nanoparticles. [139] Adding these metal nanoparticles enables 3D-printed products to have excellent mechanical properties that match the mechanical properties required for bone tissue engineering.…”
Section: Nanomaterials For Enhancing Mechanical Propertiesmentioning
confidence: 99%
“…[125] Some studies have also found that nanoparticles of different particle diameters [132] and shapes can affect the mechanical properties of materials. Besides, researchers often use metal nanoparticles to enhance the mechanical properties of polymer materials, [133] such as Fe 2 O 3 nanoparticles, [134] gold nanoparticles, [135,136] ZrO nanoparticles, [137] titanium dioxide nanoparticles [138] and CuS nanoparticles. [139] Adding these metal nanoparticles enables 3D-printed products to have excellent mechanical properties that match the mechanical properties required for bone tissue engineering.…”
Section: Nanomaterials For Enhancing Mechanical Propertiesmentioning
confidence: 99%
“…To date, additive manufacturing has proven effective in meeting the demands for prototypes, customized products, and mass production processes, especially using fused filament fabrication (FFF) MEX technology [ 6 ]. The escalating demand for products with enhanced complexity and multi-functionality across a variety of industries [ 7 ], such as engineering [ 8 ], electronics [ 9 ], aerospace [ 10 ], and the medical field [ 11 , 12 , 13 , 14 ], has led to the acceptance and integration of this technology [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The FFF technique can handle a broad range of thermoplastic filaments [ 19 ], including acrylonitrile butadiene styrene (ABS) and Polylactic Acid (PLA) [ 20 , 21 ]. Numerous studies have demonstrated that FFF manufacturing and structural factors, including printing speed, layer thickness, and temperature (at the bed, nozzle, and chamber) among others [ 19 ], are critical as they can meaningfully influence the mechanical behavior of the 3D-printed specimen and directly impact the product’s efficiency [ 15 ]. The relationship between these complex and diverse parameters and their properties has been extensively researched and analyzed [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations